TINDAK PIDANA PENCURIAN BENDA SAKRAL DI BALI - Suandi, Ari Pramitha; Ariawan, I Gst Ketut; Suardana, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2013)
Theft offenses, can be found in any society, including in Bali and is regarded asa normal phenomenon. However, in Bali theft will be an interesting issue, when theobject of theft was sacred objects. The frequency of criminal theft of sacred objects inBali, is quite high. The high frequency of criminal theft of sacred objects on the onehand can not be released to the uniqueness and value of the art of sacred objects that areattracting overseas for collecting. On the other hand, for the perpetrators of theft ofsacred objects, has a high economic value.
Keywords: offenses, sacred objects